Genetic algorithm based optimal compass alignment. Issue 2 (1st February 2016) - He, Hongyang; Jiangning, Xu; Feng, Li; Miao, Wu
Abstract : Compass alignment is an important solution for the initial alignment of strap‐down inertial navigation system (SINS). Values of parameters in compass alignment circuit have a direct influence on the performance of alignment. The optimal parameters of alignment circuit differ from one SINS to another. Traditionally, these alignment parameters are mainly determined by experience and experiments that involves a lot of trial‐and‐error. It is hard to acquire optimal parameters or achieve an optimal alignment. To solve this problem, and taking advantages of genetic algorithm (GA) of global searching, parallel computing and robustness, a GA based compass alignment approach is proposed. According to the characteristics of the compass alignment, reasonable fitness function of GA is established. Then, compass alignment parameters are optimised by GA to achieve an optimal alignment. The experimental results show that the proposed method can search out the optimal alignment parameters rapidly and improve the performance of compass alignment.